Regional Collaboration Strategy to Overcome Geopolitical Threats in the ASEAN Maritime Region - Trilia, Dewi; Mamahit, Desi Albert; Wiranto, Surya; Widodo, Pujo; Saragih, Herlina Juni Risma; Suwarno, Panji (Formosa Journal of Applied Sciences, 2024)
The ASEAN maritime region is a strategic area that faces various geopolitical threats, such as piracy, smuggling and territorial disputes. Overcoming this threat requires effective regional collaboration among ASEAN member countries. This research aims to analyze regional collaboration strategies that can be implemented to improve maritime security in ASEAN. The research methods used include qualitative analysis of existing cooperation initiatives, evaluation of the effectiveness of collaboration mechanisms, as well as interviews with experts and stakeholders in the field of maritime security. The research results show that strengthening dialogue mechanisms, increasing the capacity of member countries, developing maritime infrastructure, and collaborating with external partners are key elements in the regional collaboration strategy.